2019
DOI: 10.1088/1361-6641/ab19cd
|View full text |Cite
|
Sign up to set email alerts
|

Design of AlGaN-based lasers with a buried tunnel junction for sub-300 nm emission

Abstract: This paper discusses the design of electrically-pumped AlGaN-based in-plane lasers emitting at ∼290 nm. Our laser design utilizes strained Al 0.5 Ga 0.5 N quantum wells, and a novel polarization engineered AlGaN/InGaN/AlGaN-based tunnel junction. The low resistive tunnel junction is used as an intracavity contact in the device in place of the resistive p-type contact; which leads to improved hole injection and a reduced threshold voltage. Hence, room-temperature continuouswave laser operation could be enabled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The 2D spatial mode distribution of fundamental TE mode is shown in figure 3(b). Although previously it was suggested that an asymmetric waveguide [14][15][16] is optimum for reducing optical absorption loss in a laser structure with a heterojunction TJ having an absorbing interlayer, in this design, we opted for a symmetric waveguide structure. This choice was made because our homojunction TJ is transparent and will not absorb the light generated by the active region.…”
Section: Optical Cavity Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2D spatial mode distribution of fundamental TE mode is shown in figure 3(b). Although previously it was suggested that an asymmetric waveguide [14][15][16] is optimum for reducing optical absorption loss in a laser structure with a heterojunction TJ having an absorbing interlayer, in this design, we opted for a symmetric waveguide structure. This choice was made because our homojunction TJ is transparent and will not absorb the light generated by the active region.…”
Section: Optical Cavity Designmentioning
confidence: 99%
“…To overcome all these drawbacks, laser structures with compositionally graded transparent tunnel junctions (TJs) along with an optimized QW active region show promise. The implementation of such TJs in a laser structure allows for the replacement of the resistive p-type contact and p-AlGaN cladding layer with n-AlGaN cladding layers on both the pand n-side of the laser structure [14,15]. As n-AlGaN cladding layers have lower activation energy for dopants compared to p-AlGaN layer and can form low-resistance ohmic contacts with better current spreading, this laser structure provides improved electrical properties while maintaining low optical losses [16].…”
Section: Introductionmentioning
confidence: 99%
“…Note that lasers can be operated under optical, electrical (electrically-driven), or electron beam (electron gun) excitation. All these three approaches have been already utilized to demonstrate III-nitride-based DUV lasers [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Undoubtedly, electrically-driven laser diodes (LDs) that can deliver high optical output powers at specified wavelengths and, at the same time, are robust, reliable, and portable, are more desirable due to their durability and compactness when compared to optically- or electron-beam-pumped counterparts.…”
Section: Introductionmentioning
confidence: 99%